Plasma malondialdehyde and serum trace element concentrations in patients with active pulmonary tuberculosis - Deveci, F; Ilhan, N (Springernature, 2003)
Increased amounts of reactive oxygen species (ROS) are produced as a consequence of a phagocyte respiratory burst during pulmonary inflammation. The aim of our study was to assess the concentration of malondialdehyde (MDA) and trace metals in patients with active pulmonary tuberculosis (TB). Eighty-three subjects were enrolled into the study and prospectively divided into three groups: 22 subjects with healthy controls (group I), 21 patients with inactive pulmonary TB (group II), and 40 patients with active pulmonary TB (group III). Before beginning the therapy, plasma MDA and serum concentrations of zinc (Zn), copper (Cu), albumin, and iron (Fe) were measured. The concentration of MDA and Cu in group III were higher than in the other groups (p<0.0001). The serum Zn and albumin levels were significantly lower in group III compared with healthy controls (p<0.05). There was a positive correlation between MDA and erythrocyte sedimentation rate (r = +0.647, p<0.0001; Spearman's test). Our data indicated increased circulating levels of MDA and changed serum trace metal levels in active pulmonary TB. Trace metal levels must be closely followed during the diseases process and further studies are needed to assess the role of antioxidants as adjuvant therapy in patients with active pulmonary TB.
Keywords: tuberculosis; malondialdehyde; trace metals; albumin; erythrocyte sedimentation rate